DEVELOPMENT OF EXERCISES IN WRESTLERS THROUGH SPECIAL MOVEMENT - Javlonbek Xudoyberganov (Modern American Journals, 2025)
The Resolution of the President of the Republic of Uzbekistan, No. PQ-4881 dated 04.11.2020, “On measures to develop the national sport of wrestling and further increase its international prestige” has been developed. It is aimed at regularly organizing wrestling master classes in Bukhara, Samarkand, Khiva and other tourist destinations with the participation of winners of international wrestling sports events and ensuring their coverage through the media.
Keywords: physical activity, training, system, goal, sport, competition. special, wrestling.